POKOK PIKIRAN FILSAFAT AL-FARABI - Nuthpaturahman Nuthpaturahman; Ahmad Ahmad (Jurnal Ilmiah Ilmu Pendidikan dan Kedakwahan, 2022)
Abu Nasir al-Farabi or better known as al-Farabi is a Muslim philosopher who places the roots of philosophy in detail and systematically, and outlines his ideas for easy understanding in easy terms. Although his philosophical thought was influenced by Greek philosophical thought based solely on the philosophy of physics, al-Farabi was able to answer the problems that were transferred to the foundations of religion. Among the main points of al-Farabi's mind that play an important role in the Islamic world is about emanation, according to him, this nature occurs because of the overflow of the first form (Allah), then again the thought of metaphysics, ontology, demonstrative principles, divine science, about being, the qualities of God, epistemology, psychology, morals and ethics, prophetic theory, political philosophy, and logic